On the function of hamiltonian action for nonholonomic systems and its application to the investigation of stability - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For nonholonomic systems, we introduce the notion of the function of Hamiltonian action, with the use of which we investigate the stability of nonholonomic systems in the case where the equilibrium state under consideration is a critical point of the corresponding Lagrangian (Whittaker system).